Resistance Training Suppresses Intra-abdominal Fatty Acid Synthesis in Ovariectomized Rats - Stotzer, U. S.; Rodrigues, M. F. C.; Domingos, M. M.; Silva, G. H. G.; Duarte, F. O.; Gatto, C. V. G.; O. Duarte, A. C. G.; Shiguemoto, G. E.; Perez, S. E. A.; Selistre-de-Araujo, H. S. (International Journal of Sports Medicine, 2015)
Ovarian hormone loss is associated with a shift in fat distribution to intra-abdomin al adipose tissue (intra-AAT) depots and with lipid metabolism disorders, which predisposes individuals to developing insulin resistance. Resistance training (RT) prevents increases in intra-AAT after ovarian hormone loss. However, the molecular mechanisms underlying these changes remain unclear. We investigated the effects of ovariectomy and RT on gene expression related to lipogenesis and fat oxidation in the intra-AAT of ovariectomized rats. Sprague-Dawley rats (n=6/group) were divided into the groups: sham-sedentary, ovariectomized-sedentary, sham-RT and ovariectomized-RT. RT groups performed a 10-week climbing program on a ladder with progressive overload. Intra-AAT was subjected to morphometric and mRNA analysis. Ovariectomized-sedentary group had larger adipocytes and higher expression of peroxisome proliferator-activated receptor-γ (PPAR-γ), sterol regulatory element-binding protein-1c (SREBP-1c), stearoyl-CoA desaturase-1 (SCD-1), acetyl-CoA carboxylase (ACC), hormone-sensitive lipase (HSL) and lower expression of the oxidative carnitinepalmitoyltransferase-I (CPT-1). RT counteracted OVX-induced increases in PPAR-γ and SCD-1 and decreased SREBP-1c. ACC and HSL were downregulated in ovariectomized-RT compared with the ovariectomized-sedentary group. Ovariectomized-RT group had the highest CPT-1 gene expression. Adipocyte size decreased in ovariectomized-RT group. Results suggest that RT reduces intra-AAT adipocyte size in ovariectomized rats by suppressing intra-AAT fatty acid synthesis and enhancing fatty acid β-oxidation.
Keywords: exercise training; lipid metabolism; visceral adipose tissue; ovarian hormone deficiency